Perbandingan waste besi tulangan pelaksanaan proyek konstruksi dengan perhitungan bar bending schedule (studi kasus: proyek pembangunan M&G Villa, Jalan Pantai Berawa, Canggu, Kecamatan Kuta Utara, Kabupaten Badung – Bali) - Ida Ayu Putu Sri Mahapatni; I Wayan Artana; Made Novia Indriani; Ni Made Yuyun Praptaningsih (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2024)
Excess construction materials or waste is a waste that has an impact on the construction project budget. Planning is needed in the use of construction materials, especially reinforcing steel materials, to minimize this waste material that occurs. The aim of this research is to obtain a comparison waste reinforcing iron in project implementation with planned calculations using bar bending schedule. This research was carried out on the M&G Villa structure which has a first floor area of 187 m2 and a second floor of 218 m2 located on Pantai Berawa Road, Canggu. The type of research used is quantitative research. Data processing using bar bending schedule calculations. Based on the results of the calculations that have been carried out, it is obtained waste material using calculation planning bar bending schedule amounting to 9.72% or weighing 1,331.39 kg of the total iron requirements, meanwhile waste The material that has been implemented in construction projects amounts to 13.41% or weighing 2,215.43 kg of the total requirement for reinforcing iron. The results of this calculation show waste with planning bar bending schedule can minimize waste reinforcing iron is 3.69% of waste implementation of the M&G Villa construction project.